Educational and Psychosocial Support Needs in Lynch Syndrome: Implementation and Assessment of an Educational Workshop and Support Group. Issue 2 (12th October 2016) - Corines, Marina J.; Hamilton, Jada G.; Glogowski, Emily; Anrig, Chris A.; Goldberg, Rachael; Niehaus, Kate; Salo‐Mullen, Erin; Harlan, Megan; Sheehan, Margaret R.; Trottier, Magan; Ahsraf, Asad; Tran, Christina; et al.
Abstract: Few reports of educational and counseling support resources exist for Lynch syndrome (LS), a disorder requiring multi‐organ cancer screening and specialized medical care throughout adult life. Here we describe the development and efficacy of two resources designed to address this need, the Memorial Sloan Kettering Cancer Center Clinical Genetics Service annual Lynch Syndrome Educational Workshop (LSEW), and a quarterly Lynch Syndrome Patient Advocacy Network (LSPAN) support group. The LSEW and LSPAN were implemented beginning in 2012. Participant survey data evaluating satisfaction, clarity, and unmet needs for each event were retrospectively analyzed and summarized using descriptive statistics. Annual LSEW attendance ranged from 53 to 75 total participants. LSEW year 1 participants indicated a need for a support group, and preferred in‐person meetings at a frequency of every 3–6 months. For LSEW year 2–5 participants, >96 % reported satisfaction with the LSEW, and >82 % expressed interest in secure online support. Common themes for improvement included increased time for question and answer sessions and additional introductory genetics education. Responding LSPAN participants ( n = 57 total survey responses in 11 meetings) found the meetings helpful (100 %), information clear (91 %), and presence of a genetic counselor useful (67 %). Desired discussion topics included coping with stress and anxiety, development of a support network, family communication about LS, genetic testing decisions, and bereavement. Following genetic counseling, a need exists for ongoing educational and emotional support in LS. Implementation of resources such as the LSEW and LSPAN is feasible and perceived as helpful by participants.